Gender and geography: World views and practices - Maria Dolors Garcia Ramon; Janice Monk (Belgeo)
In introducing this theme issue on international directions in gender studies in geography, we take up three cross-cutting issues. First, we examine the importance of context in shaping where, why, how and by whom gender research is carried out, noting the importance of the representation of women in the profession, the place of geography within the social sciences, and the implications of political and economic contexts. Second, we review theoretical and methodological directions and empirical emphases. Third, we take up the politics of Anglo-American and English-language hegemonies in research publications, recognizing that hegemonies are internally as well as externally created. We suggest practices that could foster scholarship that is more inclusive intellectually and politically. We advocate theorizing that interrogates how “diversity” and “difference” are imagined; we argue for promoting both specialist research as well as the “mainstreaming” of gender perspectives; and we suggest ways of challenging the notion that English-language publications are synonymous with international prestige and value.